2018
DOI: 10.3390/en11102758
|View full text |Cite
|
Sign up to set email alerts
|

Flux-Switching Permanent Magnet Machine with Phase-Group Concentrated-Coil Windings and Cogging Torque Reduction Technique

Abstract: We herein propose a novel high-torque-density flux-switching permanent magnet machine (FSPMM) which adopted phase-group concentrated-coil (PGCC) winding and a cogging torque reduction technique. The PGCC winding was applied to increase the torque density. In order to maximize the torque of the FSPMM that utilizes the PGCC windings, the performance according to stator slots/rotor poles combinations were compared. A machine which had 12 stator slots and 13 rotor poles (12S13P) was selected for its top average to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…A time-stepping algorithm was employed and the period T f of the fundamental harmonics was divided into 1500 steps. Equations (2) and (5) were implemented in the developed model in order to perform a current waveform shape optimization. Sensors 2020, 20, x FOR PEER REVIEW 6 of 11…”
Section: Numerical Fem Model Of Pmsm and Results Of Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A time-stepping algorithm was employed and the period T f of the fundamental harmonics was divided into 1500 steps. Equations (2) and (5) were implemented in the developed model in order to perform a current waveform shape optimization. Sensors 2020, 20, x FOR PEER REVIEW 6 of 11…”
Section: Numerical Fem Model Of Pmsm and Results Of Simulationsmentioning
confidence: 99%
“…Therefore, reducing the torque ripples in electrical drive systems has been a point of interest for many research and design teams in recent decades. In this type of research, two major trends can be observed: (1) the reduction in torque ripples by the control system side [1][2][3][4][5] and (2) the improvement of the torque quality at the design stage by the optimization of the electromagnetic circuit of the electrical machine. In the first trend, the current harmonic injection is one of the commonly applied techniques [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain a reliable optimal design result, a large number of DOE have to be carried out. However, the conventional method of manually performing the process was complicated and time consuming, and thus the number of DOE was limited [10][11][12][13][14][15][16][17][18]. However, using the automated DOE process proposed in this study, not only can the DOE be easier but also the number of DOE can be dramatically increased, resulting in high reliability of the optimal design result.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies have been applied to optimal design using metamodel generated in one way. There have been a lot of optimizations recently using a single metamodeling technique such as Kriging and response surface method [10][11][12][13][14][15][16][17][18]. However, since a suitable metamodel is different according to each design problem and condition, it is necessary to select the best metamodel through accuracy evaluation after generating several metamodels.…”
Section: Introductionmentioning
confidence: 99%
“…The cogging torque is one of the most representative components of torque ripple in the permanent magnet synchronous motor (PMSM). Therefore, studies on the reduction method for the cogging torque have been actively carried out to minimize the torque ripple [1][2][3][4][5][6][7][8][9][10][11]. Those studies on cogging torques have been mainly focused on reducing the cogging effect by modulating the combination of the pole and slot number, the pole arc, the shape of the core, the skew angle, the notching, etc.…”
Section: Introductionmentioning
confidence: 99%